Passengers' Evacuation in Ships Based on Neighborhood Particle Swarm Optimization. (12th March 2014) - Yuan, Gan-Nan; Zhang, Li-Na; Liu, Li-Qiang; Wang, Kan
Abstract : A new intelligent model to simulate evacuation behavior in ships called neighborhood particle swarm optimization is proposed. This model determines the rules of behavior and velocity updating formulas to solve staff conflicts. The individuals in evacuation are taken as particles in PSO and update their behaviors by individual attributes, neighborhood attributes, and social attributes. Putting the degree of freedom movement of ships into environment factor and using the real Ro-Ro ship information and IMO test scenarios to simulate the evacuation process, the model in this paper can truly simulate the behavior of persons in emergency and provide a new idea to design excellent evacuation model.